Presence of a long accessory flexor tendon of the toes in surgical treatment for tendinopathy of the insertion of the calcaneal tendon: case report - Nelson Pelozo Gomes Júnior; Carlos Vicente Andreoli; Alberto de Castro Pochini; Fernando Cipolini Raduan; Benno Ejnisman; Moisés Cohen (Revista Brasileira de Ortopedia, 2016)
ABSTRACT The presence of accessory tendons in the foot and ankle needs to be recognized, given that depending on their location, they may cause disorders relating either to pain processes or to handling of the surgical findings. We describe the presence of an accessory flexor tendon of the toes, seen in surgical exposure for transferring the long flexor tendon of the hallux to the calcaneus, due to the presence of a disorder of tendinopathy of the insertion of the calcaneal tendon in association with Haglund's syndrome.